rTMS neuromodulation improves electrocortical functional measures of information processing and behavioral responses in autism - Sokhadze, Estate M.; El-Baz, Ayman S.; Sears, Lonnie L.; Opris, Ioan; Casanova, Manuel F. (Frontiers in Systems Neuroscience, 2014)
Objectives: Reports in autism spectrum disorders (ASD) of a minicolumnopathy with consequent deficits of lateral inhibition help explain observed behavioral and executive dysfunctions. We propose that neuromodulation based on rTMS will enhance lateral inhibition through activation of inhibitory double bouquet interneurons and will be accompanied by improvements in the prefrontal executive functions. Methods: The current study used ERPs in a visual oddball task with illusory figures. We compared clinical, behavioral and electrocortical outcomes in 2 groups of children with autism (TMS, wait-list group [WTL]). We predicted that 18 session long course in autistic patients will have better behavioral and ERP outcomes as compared to age- and IQ-matched wait-list group. We used 18 sessions of 1Hz rTMS applied over the dorso-lateral prefrontal cortex in 27 individuals with ASD diagnosis. The WTL group was comprised of 27 age-matched ASD subjects. Results: Post-TMS evaluations showed decreased irritability and hyperactivity and decreased stereotypic behaviors. Following rTMS we found decreased amplitude and prolonged latency in the fronto-central ERPs to non-targets in the TMS group. These ERP changes along with increased centro-parietal ERPs to targets are indicative of more efficient processing of information post-TMS. Another finding was increased magnitude of error-related negativity (ERN) during commission errors. We calculated normative post-error reaction time (RT) slowing response in both groups and found that rTMS was accompanied by post-error RT slowing and higher accuracy of responses, whereas the WTL group kept on showing typical for ASD post-error RT speeding and had higher error rate. Conclusion: Results from our study indicate that rTMS improves executive functioning in ASD as evidenced by normalization of ERP responses and behavioral reactions during executive function test, and also by improvements in clinical behavioral evaluations.